Gastrointestinal Motility and Gut Hormone Secretion in response to Shenhuang Plaster in a Postoperative Ileus Rat Model. (2nd June 2021) - Shi, Yanan; Zheng, Yingsong; Xu, Jingming; Ding, Bin; Shou, Qiyang; Chen, Guiping; Liu, Ting; Sun, Qiuhua; Xu, Xiaohong
Abstract : Postoperative ileus (POI), a gastrointestinal function disorder, is a complication that arises from surgery. Shenhuang plaster (SHP) application to the Shenque acupoint (CV8) to promote the recovery of gastrointestinal function has achieved definite curative effects in clinical settings; however, the underlying pharmacological mechanism remains unknown. In this study, we evaluated the effects of SHP using a Sprague Dawley rat POI model. Then, gastrointestinal transit in different rat groups was evaluated by the movement of fluorescein-labelled dextran. Ghrelin, obestatin, motilin (MTL), and vasoactive intestinal peptide (VIP) plasma concentrations were measured via a radioimmunoassay. The expression of the ghrelin and obestatin receptors (GHS-R1 α and GPR39) in the intestinal muscularis of rats in different groups was comparatively identified via western blotting. The results indicated that SHP application improved gastrointestinal motility in POI model rats. SHP application significantly increased ghrelin concentration and the expression of its receptor and inhibited obestatin concentration and the expression of its receptor in blood. Further, ghrelin concentration and the capability of gastrointestinal transit were positively correlated. Simultaneously, SHP application also promoted the secretion of other gastrointestinal motility hormones, such as MTL and VIP. Hence, these results provide evidence that SHP can promote the recovery of gastrointestinal transmission in POI rat models through regulation of ghrelin and other intestinal hormones.